Evaluasi Kualitas pada PCB Hasil Proses Immersion Tin - Vivin Octowinandi; Fadli Firdaus; Ridwan Ridwan; Diono Diono; Rifqi Amalya F; Muhammad Naufal Airlangga Diputra; M Rif'an Maulana (Politeknik Negeri Batam, 2023)
The PCB manufacturing process involves many processes, one of which is Surface finishes. One type of Surface finishes commonly used is Immersion tin. Immersion tin is a Surface finishes process that uses pure tin in the process. Immersion tin protects the copper from oxidation and makes the copper surface or pad easy to solder. The cleanliness of the pad and the thickness of the Immersion tin affect the quality of the PCB produced. Therefore, the researchers evaluated the quality of the results of the Immersion tin process using the DOE (Design of Experiment) method. Where this method can help in determining the optimal parameters. The variables used are Storage Time After Microetch and Immersion in tin Bath. In the research process it was found that PCBs underwent morphological changes at 23 hours after being stored in storage. This is caused by the presence of moisture that is still present on the PCB as a result of not being optimal during the drying process. In this study, the optimal Solder Coating Thickness in the 14th sample was 4.59 Âµm and with the parameters Storage Time After Microetch for 50 minutes and Immersion in tin Bath for 120 minutes. For the most optimal pad cleanliness found in the 5th and 12th samples with the Storage Time After Microetch parameter for 30 minutes and 60 minutes and marked by the absence of contaminants on the pad. In addition, in this study there were less than optimal mapping results marked by only 1 part of 1 sample containing tin from 16 test samples. The sample is the 3rd sample with the parameter Storage Time After Microetch for 10 minutes and Immersion in tin Bath for 55 minutes with a tin content of 91.9%.